The definitive collection [compact disc] - Berry, Chuck (Geffen/Chess, 2006)
More than any other artist, Chuck Berry cooked up the basic recipe for rock n' roll. With his guitar style, Berry would have many hit songs, including Johnny B. Goode and Maybellene, which are just two of the hits included in this collection.